Effects of dust fall on stigma and pollination and fertilization process of female flower in pistachio pistachii - ZHOU Xinyu; WANG Fengbo; Amanula Yimingniyazi; WANG Tian; Batur Bake (Guoshu xuebao, 2025)
[Objective] Southern Xinjiang is a major cultivation area for pistachios and also a region prone to dust storms. Natural dustfall after dust storms is mostly concentrated in spring and summer, overlapping with the flowering period of pistachios. The study aimed to explore the impact of dust deposition on the reproductive process of pistachios in order to provide a theoretical basis for improving fruit setting rate and fruit quality. [Methods] The Kerman variety of pistachio, the main cultivated fruit tree in Shufu County, Kashgar Region, Xinjiang, was used as experimental material. The female inflorescences located on the sunny side of the trees in the center of the orchard were bagged during their bud burst period. Based on the measured data of dustfall amounts during the flowering period in southern Xinjiang, the thickness of dustfall covering was set. The artificial dustfall covering method was adopted, with the treatments of 0.3 mg·cm-2 (mild), 0.8 mg·cm-2 (moderate), and 1.3 mg·cm-2 (severe) of dustfall covering thickness and artificial bagging for dust prevention as the control (CK). The natural floating dust was collected as the dust source for the simulation experiment. A handheld dust applicator was used to evenly spread the required thickness of dustfall on each inflorescence. At 20:00 every day, the bags were opened to spray dust on the female flowers, and the artificial dustfall treatment ended before the pollination of the female flowers. The samples were taken during the full-blooming stage. The scanning electron microscope was used to observe the differences in the ultrastructural morphology of the stigmas under the control and dustfall covering. The benzidine-hydrogen peroxide method was applied to study the strength of the stigmatic receptivity of the female flowers under the control and dustfall covering. The continuous sampling was carried out every 0.5 hours after pollination during the full-bloom stage of the female flowers, and the fluorescence microscope was used to observe the differences in the process and duration of the growth of pistachio pollen tubes under the control and dustfall covering. [Results] In the dust-free control, the papilla cells of the stigmas of female flowers were clearly distinguishable, with relatively regular cell shapes, closely and orderly arranged, and very plump. The contact area between their surfaces and the air was relatively large. After mild and moderate dustfall treatments, the surfaces of the stigmas of the female flowers were covered by dustfall particles, and the moisture on the stigma surfaces was absorbed, causing obvious wrinkling and atrophy of the papilla cells. Aafter severe dustfall covering, the papilla cells on the stigma surfaces shrank severely, and the stigma surfaces were difficult to clearly distinguish. The dustfall treatments would weaken the stigmatic receptivity. The stigmas of female flowers in the control had the strongest receptivity, with a darker color around the stigmas and a large number of continuous large and small bubbles on the surfaces. The stigmas of female flowers under mild dustfall covering had relatively strong receptivity, with the color around the stigmas turning dark and closely connected small bubbles attached on the surfaces. The stigmas of female flowers under moderate dustfall covering had relatively weak receptivity, with an unobvious color change around the stigmas and a small number of bubbles generated. The stigmas of female flowers under severe dustfall covering had the weakest receptivity, with no color change around the stigmas, very few bubbles on the surfaces, and some even stopped reacting without any bubbles. The dustfall covering also affected the elongation speed of the pollen tubes and prolonged the time for pistachio to complete fertilization. The elongation speed of the pollen tubes in the dustfall-treated plants was lower than that in the dust-free control plants, and the amount of pollen entering the embryo sac in the control plants was significantly more than that in the dustfall-treated plants. The plants of the control completed fertilization 3 hours after pollination. Compared with the control, the mild dustfall caused a 0.5-hour delay in the completion of fertilization of the female flowers; the moderate dustfall caused a 1-hour delay; and the severe dustfall caused a 2-hour delay. [Conclusion] During the flowering period, the dustfall treatments could cause wrinkling and damage to the cells of the stigmas of the female flowers, reduce the stigmatic receptivity, and prolong the time to complete fertilization.